STATISTIK DEMOGRAFI DIAPHANIA INDICA SAUNDERS (LEPIDOPTERA: CRAMBIDAE) - Ita Fitriana; Darmayanti Buchori; Ali Nurmansyah; Roschon Ubaidillah; Akhmad Rizal (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Demographic statistic of Diaphania indica Saunders (Lepidoptera: Crambidae). Diaphania indica is a pest of Cucumis sativus L. The information about the biology of D. indica is needed to determine appropriate pest management strategies. The aim of this study was to study the biology and life cycle of D. indica. The study was conducted by observing life stage development of D. indica, such as life cycle, head width and body length. The life table was determined by calculating mortality of D. indica individuals and fecundity at each age. Mortality and fecundity data of D. indica were then used to calculate the parameters of population growth including gross reproduction rate (GRR), net reproductive rate (Ro), mean generation time (T) and and intrinsic rate of increase (r ). The results show that the life cycle of D. indica is about 25.7 days, while egg stadium = 3.2 days, larval stadium = 13.5 days, pupal stadium = 7.9 days, imago stadium = 8.6 days, and preoviposition period = 3.9 days. GRR of D. indica is 263 individuals per generation. Ro = 51 individuals per female per generation. T is 31.3 days and the innate capacity for increase (r) = 0.1 individual per female per day.